2020
DOI: 10.1039/d0cc01456g
|View full text |Cite
|
Sign up to set email alerts
|

Atomically thin TiO2 nanosheets synthesized using liquid metal chemistry

Abstract: The library of two-dimensional materials is limited since many transition metal compounds are not stratified and can thus not be easily isolated as nanosheets. Liquid metal-based synthesis provides a new approach to overcome this limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…High‐resolution imaging reveals that the TiO 2 nanosheets are of highly crystallinity. [ 86 ] These 2D TiO 2 nanosheets can be implemented as gate dielectric in modern nano‐electronics.…”
Section: Fabrication Strategies Of 2d Metal Oxides Via Liquid Metalsmentioning
confidence: 99%
“…High‐resolution imaging reveals that the TiO 2 nanosheets are of highly crystallinity. [ 86 ] These 2D TiO 2 nanosheets can be implemented as gate dielectric in modern nano‐electronics.…”
Section: Fabrication Strategies Of 2d Metal Oxides Via Liquid Metalsmentioning
confidence: 99%
“…This value is consistent with the ultrathin nature of nanosheets that can be produced using a similar approach from metals alloyed with galinstan reported previously that included the much more reactive metals of Gd, Hf and Al which all produced nanosheets less than 1.1 nm in thickness, 21 and Ti with nanosheets of 2 nm thickness. 42 Even though thermodynamically the oxidation of Ga is preferred, as DG f of CoO is much higher at À214.2 kJ mol À1 , the presence of 10 mM HCl results in the dissolution of any gallium oxides that are formed which subsequently promotes CoO x formation. The conditions are also appropriate for the existence of CoO x in this solution as previous work has shown that CoO only begins to dissolve to a signicant extent at concentration of 0.5 M HCl.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, pure liquid metals and their alloys were used as synthesis medium or directly employed to carry out a facile and liquid‐phase free exfoliation to synthesize high‐quality and scalable 2D nanomaterials via either i) air‐injection or ii) sonication‐assisted method ( Figure ). [ 18 ] These are some innovations in synthesizing 2D nanomaterials particularly for those which have not intrinsic layered crystal structures (i.e., numerous metal oxides [ 18a,19 ] ) or those which, having strong interaction between their crystal layers (i.e., bismuth [ 18e ] ). Synthesis of these 2D nanomaterials is rather difficult using conventional approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of the chemical reaction between liquid metal surface and oxygen under reactive ambient conditions is based on the observation of the self‐limiting oxide layers formation. [ 20 ] Investigation shows that the surface of pure or liquid metal alloys such as pure gallium (Ga) [ 18a ] or gallium‐1 wt% titanium (Ga‐1 wt% Ti), [ 19 ] are composed of gallium oxide (Ga 2 O 3 ) or preferentially titanium dioxide (rutile TiO 2 ), respectively, despite the presence of a huge amount of Ga element in the case of Ga‐1 wt% Ti alloy composition. The prediction of the formed metal oxide layer in co‐alloyed metals could be done based on thermodynamic considerations such that the oxide with the largest reduction of Gibbs free energy (Δ G f ) first form on the liquid metal alloy surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation